Ultrasonic-assisted extraction of luteolin from peanut shells using ionic liquid and its molecular mechanism - Liwei Niu; Siwen Zhang; Xiaoyu Si; Yuhan Fang; Shuang Wang; Lulu Li; Zunlai Sheng (Ultrasonics Sonochemistry)
This study investigates the potential of ionic liquids (ILs) as sustainable solvents in ultrasonic-assisted extraction (UAE) to efficiently recover luteolin from peanut shells. Among the range of ILs tested, 1-butyl-3-methylimidazolium tetrafluoroborate stood out as the most effective solvent, achieving the highest extraction yield. Single-factor experiments were conducted to analyze the effects of ultrasonic power, extraction time, extraction temperature, IL concentration, and solid-to-liquid ratio on extraction efficiency. Further optimization of the extraction conditions was performed using response surface methodology and neural network analysis, resulting in a significantly enhanced luteolin yield of 3.71 ± 0.06 mg/g. Interaction energy analyses were conducted to elucidate the interactions between ILs and luteolin, confirming the experimental findings and highlighting the strongest interaction energy between 1-butyl-3-methylimidazolium tetrafluoroborate and luteolin. A kinetic model for luteolin extraction was developed, demonstrating that the extraction process follows a second-order rate model, where the extraction rate is directly proportional to the square of the concentration difference between luteolin and the solvent. The outcomes of this research present an efficient protocol for luteolin extraction and provide novel insights into the application of UAE in extracting natural products.